Analysis Of The Application Of Learning Methods Used Teachers In Learning Ski At Mtsn 2 Bengkulu City - Hensi Tri Arni; Midela Eka Putri; Nadya Amalia; Alimni (JPT : Jurnal Pendidikan Tematik, 2026)
Learning methods in schools are very varied and many kinds. Teachers are required to be able to apply appropriate learning methods to their students. The application of appropriate learning methods greatly determines success in the learning process so that the objectives of the learning can be achieved properly according to the existing curriculum. Especially in the learning process on Islamic Cultural History subjects. The problem that will be answered in this study is how to apply the Islamic Cultural History learning method at Madrasah Tsanawiyah Negeri 2 Bengkulu City. The subjects in this study were teachers who taught Islamic Cultural History at Madrasah Tsanawiyah Negeri 2 Bengkulu City. Data collection was carried out through observation of Islamic Cultural History learning activities and interviews with research subjects. After the data is collected, the data is then analyzed descriptively qualitatively. The results showed that the types of methods used in learning Islamic Cultural History at Madrasah Tsanawiyah Negeri 2 Bengkulu City were lecture, question and answer, discussion, and assignment methods.